PEMAHAMAN METODE PENELITIAN BERBASIS EVIDENCE BASED PRACTICE IN NURSING PADA MAHASISWA KEPERAWATAN - Lilik Pranata; Legiran; Vincencius Surani; Keristina ajul; Ketut Suryani; Aniska Indah Fari (Jurnal Kesehatan dan Pembangunan, 2023)
Evidence-based practice in nursing is a method used to combine research results with clinical experience and values believed by patients and their families in nursing actions that aim to improve the results of nursing care for patients. Students should also be able to apply and have good knowledge of the concept of Evidence-based Practice in nursing in providing comprehensive nursing care, in order to accelerate the patient's healing process. The aim is to determine the understanding of research methods based on evidence-based practice in nursing in nursing students. This research is a descriptive survey research. The research was conducted in May 2023 and the sample in the study was nursing profession students in one of the health education in Palembang city, with a total sample of 41 active students who served in the hospital. the results showed that students' understanding of Evidence-based Practice In nursing with a good categorical as many as 2 people (5%), enough 17 people (42%) and less 22 people (51%). Conclusion, the results indicate the need for assistance to students so that students understand about Evidence-based Practice In nursing. Suggestions for health education institutions provide intensive assistance to students who are committed to applying Evidence-based Practice in nursing.